The trend of neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in spontaneous intracerebral hemorrhage and the predictive value of short-term postoperative prognosis in patients - Zhang, Jian; Liu, Chunlong; Hu, Yaofeng; Yang, Aoran; Zhang, Yonghui; Hong, Yang (Frontiers in Neurology, 2023)
Background: Neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) play an important role in the inflammatory response in various diseases, but the role in the course of spontaneous intracerebral hemorrhage (ICH) is unclear.Method: This study retrospectively collected baseline characteristics and laboratory findings, including NLR and PLR at different time points, from spontaneous ICH patients undergoing surgery between January 2016 and June 2021. Using the modified Rankin Scale score (mRs) to group survival status of patients at 30 days after surgery, trends in NLR and PLR during ICH were analyzed. Multivariate logistic regression analysis was used to identify independent risk factors affecting the prognosis of ICH patients at 30 days after surgery.Results: A total of 101 patients were included in this study, and 59 patients had a poor outcome at 30 days after surgery. NLR and PLR gradually increased and then decreased, peaking at 48h after surgery. Univariate analysis demonstrated that admission Glasgow Coma Scale (GCS) score, interval from onset to admission, hematoma location, NLR within 48h after surgery and PLR within 48h after surgery were associated with poor 30-day prognosis. In multivariate logistic regression analysis, NLR within 48h after surgery (OR, 1.147; 95% CI, 1.005, 1.308; P, 0.042) was an independent risk factor for 30-day after surgery prognosis in spontaneous ICH patients.Conclusion: NLR and PLR showed a trend of increasing and then decreasing in the process of ICH. High NLR within 48h after surgery was an independent risk factor for poor prognosis 30 days after surgery in spontaneous ICH patients.